Pelatihan Penjernihan Minyak Jelantah Pada Ibu PKK Desa Labuhan Sumbawa, Kec. Labuhan Badas, Kabupaten Sumbawa - Nurlaila Agustikawati; Fitri Setianingsih; Desy Fadilah Adina Putri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Used cooking oil is oil that has decomposed fatty acids at certain limits so that it becomes unfit for use. Used cooking oil is obtained from the process of cooking or heating food using oil repeatedly and at high temperatures. The behavior that is often carried out by the community is that after being used repeatedly, the used cooking oil will be immediately dumped into the ground, ditches, pipelines or waters. This can result in environmental pollution in the form of death of aquatic biota, organisms in the soil, closing soil pores, contaminating groundwater and even increasing COD and BOD in soil and water. This type of community service is classified as expert service, namely community service carried out by lecturers in accordance with their field of knowledge, in this case through training activities in the pursuit of waste cooking oil using practical methods. The results of this service increase knowledge of the physical characteristics of cooking oil damage, the dangers of repeated use of oil, knowledge of waste used cooking oil management, and increased knowledge of waste used cooking oil utilization